Analisis Kesalahan Penggunaan Adjektivdeklination Bahasa Jerman - Yuyun Sadaali; Syarifah Fathimah (Universitas Negeri Makassar, 2022)
Abstract. This study aims to obtain data on the types of errors in the use of adjectives im bestimmten Articles und unbestimmten Articles nominative and accusative cases of XII grade students of SMA Negeri 16 Makassar. The type of research used is descriptive qualitative. The data collection technique used is a test. The data sources of this research were the students of class XII SMA Negeri 16 Makassar, totaling 28 students. The sampling technique of this research is Total Sampling. The results of data analysis showed that the total errors in the use of Adjective declination im bestimmten Articles of nominative and accusative cases and Im unbestimmten Articles of nominative and accusative cases were 256 errors. The types of errors that exist are the types of errors in the use of the Adjektivdeklination im bestimmten Article in the nominative case, 39 errors, and the accusative case, 28 errors. Then Adjektivdeklination im unbestimmten Articles on the nominative case of 48 errors and for the accusative case of 141 errors. The error rate of using adjectives of class XII students of SMA Negeri 16 Makassar is included in the fairly high category.Keywords: Error Analysis, German, Adjektivdeklination